Automation and Robotics in Biosensing for Early Diagnosis and Monitoring of Peri-Implantitis – A Systematic Review. (Bangladesh Journal of Medical Science, 2026)
Background Peri-implantitis is a progressive inflammatory illness that affects implant longevity. Early detection and continuous monitoring are crucial for efficient management. Recent breakthroughs in biosensing, automation, and robotics offer exciting prospects. The purpose of this systematic review is to assess the effectiveness of automation and robotic-assisted biosensing technologies in the early detection and real-time monitoring of peri-implantitis. Methods A complete search of PubMed, Scopus, Cochrane Library, IEEE Xplore, and Web of Science (2013- 2024) was carried out. Studies that used biosensors with automated or robotic systems to diagnose periimplantitis were considered. Methodological quality was evaluated using the PRISMA and ROBIS methods. Results 34 out of 562 articles met the requirements. Biosensing platforms (optical, electrochemical, piezoelectric) with AI integration demonstrated great sensitivity (80-95%) and specificity (85-98%) in detecting early biomarkers such as IL-1β, TNF-α, and MMPs. Robotic systems improved reproducibility and patient comfort. Conclusion While promising, more clinical validation and standardization are required for general implementation.Bangladesh Journal of Medical Science Vol. 25. Supplementary Issue 2026, Page : S18-S25